Polymyxins resistance: old antimicrobials, last therapeutic options - Raquel Girardello; Ana Cristina Gales (Universidade de Santa Cruz do Sul, 2012)
Polymyxins are polypeptide antimicrobials that act in the cell membranes and promote decrease of the cell wall integrity. These antimicrobials are used in the clinical practice for treatment of the multi-drug resistant Gram negative bacilli infections as the last therapeutic option. The polymyxin resistance involves lipopolysaccharide modifi cations that decrease the affi nity of the antimicrobial with the cell surface. These modifi cations are regulated by two component systems that are active by environmental infl uences as cation presence, pH or polymyxin exposure. The environmental infl uences initiate the action of the genes that develop the polymyxins resistant phenotype. The polymyxins viability maintenance is essential for the treatment for multi-drug resistant bacilli infections, while new therapeutic options are not available.KEYWORDS polimixins antimicrobial resistance